Talk and Action: What Individual Investors Say and What They Do - Dorn, Daniel; Huberman, Gur (Review of Finance, 2005)
Abstract Combining survey responses and trading records of clients of a German retail broker, this paper examines some of the causes for the apparent failure to buy and hold a well-diversified portfolio. The subjective investor attributes gleaned from the survey help explain the variation in actual portfolio and trading choices. Self-reported risk aversion is the single most important determinant of both portfolio diversification and turnover; other things equal, investors who report being more risk tolerant hold less diversified portfolios and trade more aggressively. Less experienced investors similarly tend to churn poorly diversified portfolios. The effect of perceived knowledge on portfolio choice is less clear cut; holding other attributes constant, investors who think themselves knowledgeable about financial securities indeed hold better diversified portfolios, but those who think themselves more knowledgeable than the average investor churn their portfolios more.